2018
DOI: 10.4314/ahs.v18i3.28
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid profile and LDH Isoenzymes as prognostic biomarkers for diabetic and/or obese subjects

Abstract: BackgroundThis study aimed to evaluate the levels of thyroid hormones and lactate dehydrogenase (LDH) isoenzymes in obese and/or diabetic patients.Subjects and methodsForty male subjects categorized into four equal groups; group 1: Non obese control subjects, group 2: Subjects suffering from type 2 diabetes mellitus (T2DM), group 3: Obese subjects (BMI ≥ 30 kg/m2) and group 4: Subjects thatwere obese and had type 2 diabetes mellitus (T2DM). Liver, kidney, lipid, thyroid hormones, total LDH and LDH isoenzymes l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
3
11
0
Order By: Relevance
“…HDL was significantly lowest in DM-OB group, followed by NDM-OB group, followed by DM-NOB group and highest in NDM-NOB group. These results are in full agreement with the study of Johari et al [17] which has similar design to our study and found corresponding results.…”
Section: Discussionsupporting
confidence: 94%
“…HDL was significantly lowest in DM-OB group, followed by NDM-OB group, followed by DM-NOB group and highest in NDM-NOB group. These results are in full agreement with the study of Johari et al [17] which has similar design to our study and found corresponding results.…”
Section: Discussionsupporting
confidence: 94%
“…There are some supporting results in the literature showing that HFD did not increase total cholesterol in all rat studies [36]. Furthermore, it is known that some obese patients have healthy lipid profile [37][38][39]. Thus, obesity likely leads to dyslipidemia, but not necessarily in all obese subjects.…”
Section: Discussionmentioning
confidence: 59%
“…There are some supporting results in the literature showing that HFD did not increase total cholesterol in all rat studies [36]. Furthermore, it is known that some obese patients have healthy lipid profile [37,38,39]. Thus, obesity likely leads to dyslipidemia, but not necessarily in all obese subjects.…”
Section: Discussionmentioning
confidence: 68%